Independent and joint association of N-terminal pro-B-type natriuretic peptide and left ventricular mass index with heart failure risk in elderly diabetic patients with right ventricular pacing - Yu, Yu; Huang, Hao; Cheng, Sijing; Deng, Yu; Liu, Xi; Gu, Min; Chen, Xuhua; Niu, Hongxia; Cai, Chi; Hua, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background Elevated levels of N-terminal pro-B natriuretic peptide (NT-proBNP) and left ventricular hypertrophy (LVH) are independent risk factors for heart failure (HF). In addition, right ventricular pacing (RVP) is an effective treatment strategy for bradyarrhythmia, but long-term RVP is associated with HF. However, there is limited evidence on the independent and combined association of NT-proBNP and left ventricular mass index (LVMI) with HF risk in elderly diabetic patients with long-term RVP. Methods Between January 2017 and January 2018, a total of 224 elderly diabetic patients with RVP at Fuwai Hospital were consecutively included in the study, with a 5-year follow-up period. The study endpoint was the first HF readmission during follow-up. This study aimed to explore the independent and joint relationship of NT-proBNP and LVMI with HF readmission in elderly diabetic patients with long-term RVP, using a multivariate Cox proportional hazards regression model. Results A total of 224 (11.56%) elderly diabetic patients with RVP were included in the study. During the 5-year follow-up period, a total of 46 (20.54%) patients suffered HF readmission events. Multivariate Cox proportional hazards regression analysis showed that higher levels of NT-proBNP and LVMI were independent risk factors for HF readmission [NT-proBNP: hazard risk (HR) = 1.05, 95% confidence interval (CI): 1.01–1.10; LVMI: HR = 1.14, 95% CI: 1.02–1.27]. The optimal cut-off point of NT-proBNP was determined to be 330 pg/ml by receiver operating characteristic (ROC) curve analysis. Patients with NT-proBNP > 330 pg/ml and LVH had a higher risk of HF readmission compared to those with NT-proBNP ≤ 330 pg/ml and non-LVH (39.02% vs. 6.17%; HR = 7.72, 95% CI: 1.34–9.31, P < 0.001). Conclusion In elderly diabetic patients with long-term RVP, NT-proBNP and LVMI were associated with the risk of HF readmission. Elevated NT-proBNP combined with LVH resulted in a significantly higher risk of HF readmission.